Upaya Meningkatkan Teknik Dasar Passing Bawah Permainan Bola Voli Melalui Penerapan Model Pembelajaran TGT (Teams Games Tournament) Pada Siswa Kelas Viii SMP Swasta Madani - Elvan Ndruru; Ignasius Ivan Kurnia Ndruru; Lukman Nasution; Joko Priono (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
This study aims to improve the learning outcomes of volleyball overhead passing through the application of the TGT (Teams Games Tournament) type cooperative learning model. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The subjects of this study were 25 students of grade VIII of Madani Mariendal 1 Medan private junior high school. The problem in this study is the low ability of students in performing volleyball underhand passing techniques as indicated by the inaccurate body position, hand movement coordination, and low student learning outcomes in physical education subjects. Therefore, a learning model is needed that can improve student activity, cooperation, and learning motivation. Data collection techniques are carried out through observation, learning outcome tests, and documentation. Data analysis is carried out descriptively quantitatively based on the percentage of student learning completion. The results of the research from the pre-test cycle I were only 8 students (32%), while the post-test cycle I increased to 12 students (48%). In cycle II it increased to 22 students (88%). Students' activities became more active, enthusiastic and enthusiastic when practicing learning, more orderly and able to cooperate with other students. Based on the results of the study, it can be concluded that the application of the Teams Games Tournament (TGT) learning model is effective in improving the basic techniques of underhand passing in volleyball in class VIII students of Madani Private Middle School. This learning model is able to create an active, fun learning atmosphere and encourage cooperation between students so that it has a positive impact on improving physical education learning outcomes.